Quantitative determination of the leaching range of in-situ leaching mining area by stagnation point - Chong Zhang; Yongmei Li; Yuqing Niu; Kaixuan Tan; Tingting Xie; Yixuan Yao; Chunguang Li; Zhenzhong Liu (Nuclear Engineering and Technology)
The leaching range is critical to the leaching efficiency, production cost and environmental effect of in-situ leaching of uranium. In this study, the groundwater dynamics of the well-site was simulated to determine the leaching range in condition of different process parameters (such as drilling space and the pumping-injection ratio), in addition, the control factors and evolution rules of the leaching boundary were explored. The results show that there is an obvious water level trough, i.e., the “stagnation point”, outside the injection hole of the well-site of in-situ leaching. The hydraulic gradient of the stagnation point is zero, which indicates that the leaching solution can migrate the farthest to stagnation point outside the well. Therefore, the connection line of all the stagnation points quantitatively determines the outer boundary of the leaching range from the perspective of hydrodynamics. Reducing the spacing of borehole can increase the drawdown of groundwater, and slightly increase the distance between the stagnation point and the edge injection well, i.e., the outer boundary of the leaching range. However, increasing the pumping-injection ratio would significantly reduce the outer boundary of the leaching range.